SOLAR ENERGY ADOPTION IN DEVELOPING COUNTRIES: OPPORTUNITIES AND CHALLENGES - Md Shahdat Hossain; Fahmina Afrin (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: The solar power in third world economies is a radical prospect to mitigate energy poverty, boost economic development and improve on environmental sustainability. Method: The lack of access to good electricity, especially rural and remote locations, has limited social and economic growth, and as a result, decentralized solar systems can serve as an alternative to traditional electricity systems. Although it has potential, solar energy has various issues that hinder its mainstream application. The factors affecting adoption include societal ones, such as community skepticism and perceived external pressures, and geopolitical considerations in terms of equity and climate justice make international cooperation more complex. Results: Not only does solar energy satisfy increasing energy needs, but it also helps to reduce climate change through less reliance on fossil fuels and a decrease in greenhouse gases. Integration and scalability are hindered by technological constraints, old infrastructure and lack of technical know-how. The lack of financial resources, excessive initial investment, and complicated international funding environment also limit the projects. The uncertainty of investors and developers is produced by policy and regulatory barriers and the discrepancy between national strategies and the needs of the local communities. Effective examples of successful projects in places like Rwanda, Kenya, and Bangladesh have shown that proper solar programs can reduce energy poverty, generate jobs and enhance education and health outcomes. Novelty: Future opportunities are based on the technological innovation, energy storage and smart grid system investments and the creation of inclusive financing systems. With a solution to these obstacles and opportunities, solar energy in developing nations has the potential to contribute to sustainable development objectives, to improve energy security and quality of life of millions, and to make renewable energy a key element of the future socio-economic and environmental stability.